On the influence of T-Stress on photoelastic analysis under pure mode II loading - Mahnaz Zakeri; Chiara Colombo (Fracture and Structural Integrity)
According to the classical definition for in-plane modes of crack deformation, the constant stress term T exists only in the presence of mode I. However, recent studies show that this term can exist in mode II conditions as well, and significantly affect the elastic stress field around the crack tip. These effects can be visualized using the experimental method of photoelasticity. Based on the analytical studies, presence of the T-stress in mode II cracks transforms the isochromatic fringe patterns from symmetric closed loops to asymmetric and discontinuous shapes. In this paper, presence of the T-stress in mode II cracks and its effects on the fringe patterns is experimentally investigated. The test specimens are Brazilian disks containing very sharp central cracks: experimental results indicate that these specimens contain negative values of T-stress. Experimental values are then compared to numerical results. To better understand the differences between experimental and numerical values, a thee dimensional analysis is performed with the finite element method: results show the influence of the real geometry of the crack front on the stress intensity factors.